APOE4 carrier identification, genetic disclosure and amyloid status: Results from the generation 2 program Alzheimer's disease prevention clinical trial at Glasgow Memory Clinic: Developing topics. (7th December 2020) - Lynch, Jennifer; Hendry, Kirsty; Lee, Emma; Wallace, Lorna; Williamson, Susan; Main, Laura; Cranmer, Alison; Inglis, Fraser
Abstract: Background: Research has demonstrated that the APOE‐ ε 4 genotype is a genetic risk factor for Alzheimer's Disease (AD) and individuals with this genotype are also at increased risk of having higher levels of β‐amyloid (Aβ); a neurochemical indicator of AD. [1]The Generation 2 Study, co‐sponsored by Novartis, Amgen and the Banner Alzheimer Institute, investigated the impact of experimental medications on Aβ levels and whether this can result in later onset of AD in those identified as having higher genetic risk. Here, we show the Generation 2 Study screening activity completed at Glasgow Memory Clinic until the early cessation of this clinical trial. Method: To identify subjects with the APOE‐ ε 4 variant of this gene, a high‐volume screening route was used. Buccal swabs were obtained and analysed. Those who were identified as having at least one copy of the APOE‐ ε 4 genotype were invited to participate in the Generation program at Glasgow Memory Clinic. The Generation 2 Study pre‐dominantly focused on the recruitment of carriers of one copy of the APOE‐ ε 4 allele. An elevated Aβ result was also required, as measured by a PET scan and/or lumbar puncture procedure, to be eligible for randomisation. Result: 3672 buccal swabs were obtained during recruitment for the Generation program. Of these, 1056 were heterozygous for APOE‐ ε 4. 653 were screened and disclosed as heterozygous for APOE‐ ε 4 with 421 of these subjects enrolled in the Generation 2 Study. 223 subjects attended for amyloid testing. It was found that 72 subjects (32%) had elevated amyloid level as determined by PET scan or lumbar puncture. 61 subjects were randomised into the Generation 2 Study at the time of early termination of this clinical trial. Conclusion: The Generation 2 Study enabled the effective identification of previously unidentified APOE‐ ε 4 carriers with elevated Aβ. This site's screen fail rate was as anticipated with the majority of screen fails due to non‐elevated amyloid results.